Effects of Exposure Duration to Cottonseed Cake-Based Diets on Broiler Performance - Adeyemo, G.O. (International Journal of Poultry Science, 2010)
Two experiments were separately conducted using cottonseed cake-based diets to feed table birds. In the first experiment (phase 1) broiler birds were fed from day old to 8 weeks of age, while in the second experiment (phase 2), the birds were fed cottonseed cake based diets from 4-8 weeks of age. Five dietary treatments were fed in both experiments formulated to be iso-caloric and iso-nitrogenous with Cottonseed Cake (CSC) replacing Soyabean Cake (SBC) at 0, 25, 50, 75 and 100% respectively. The live weight of broilers in the phases differed significantly (p